One-pot synthesis of nanochain particles for targeting brain tumors. Issue 27 (4th July 2017) - Perera, V. S.; Covarrubias, G.; Lorkowski, M.; Atukorale, P.; Rao, A.; Raghunathan, S.; Gopalakrishnan, R.; Erokwu, B. O.; Liu, Y.; Dixit, D.; Brady-Kalnay, S. M.; Wilson, D.; et al.
Abstract : To synthesize multi-component nanochains, we developed a simple 'one-pot' synthesis, which exhibited high yield and consistency. Abstract : To synthesize multi-component nanochains, we developed a simple 'one-pot' synthesis, which exhibited high yield and consistency. The nanochains particles consist of parent nanospheres chemically linked into a higher-order, chain-like assembly. The one-pot synthesis is based on the addition of two types of parent nanospheres in terms of their surface chemical functionality ( e.g., decorated with PEG-NH2 or PEG-COOH). By reacting the two types of parent nanospheres at a specific ratio (∼2 : 1) for a short period of time (∼30 min) under rigorous stirring, nanochains were formed. For example, we show the synthesis of iron oxide nanochains with lengths of about 125 nm consisting of 3–5 constituting nanospheres. The chain-like shaped nanoparticle possessed a unique ability to target and rapidly deposit on the endothelium of glioma sites via vascular targeting. To target and image invasive brain tumors, we used iron oxide nanochains with the targeting ligand being the fibronectin-targeting peptide CREKA. Overexpression of fibronectin is strongly associated with the perivascular regions of glioblastoma multiforme and plays a critical role in migrating and invasive glioma cells. In mice with invasive glioma tumors, 3.7% of the injected CREKA-targeted nanochains was found in gliomas within 1 h. Notably, the intratumoral deposition of the nanochain was ∼2.6-fold higher than its spherical variant. Using MR imaging, the precise targeting of nanochains to gliomas provided images with the exact topology of the disease including their margin of infiltrating edges and distant invasive sites.